The effectiveness of capital controls and macroprudential measures - Junyong Lee; Kyounghun Lee; Frederick Dongchuhl Oh (KDI Journal of Economic Policy, 2023)
We review the literature on the effectiveness of capital controls and macroprudential measures. First, we explain the purposes and examples of capital controls and macroprudential policies. We then analyze various theoretical models and empirical findings from prior studies that investigate the effectiveness of each instrument. Moreover, we review several studies that directly compare the two instruments and discuss whether policymakers should implement capital controls or macroprudential measures to overcome financial crises. Finally, based on a discussion of the findings of previous studies, we suggest several possible avenues for future research.
Keywords: F38; G15; G28; 330; Capital Control; Macroprudential Measure; Financial Crisis